Cyclin-dependent kinase 21 is a novel regulator of proliferation and meiosis in the male germline of zebrafish. Issue 4 (April 2018) - Webster, Kaitlyn A; Henke, Katrin; Ingalls, Delaney M; Nahrin, Adeeba; Harris, Matthew P; Siegfried, Kellee R
Abstract : Germ cell differentiation and maintenance relies on complex regulation of mitotic and meiotic progression. Cyclin-dependent kinases (CDKs) and their activating cyclin partners are known to have specialized roles in regulating cell cycle progression across tissues, including germ cells. Very little is known about CDK/cyclin function in zebrafish or the regulation of germ cell maintenance and differentiation. In a forward genetic screen for gonadogenesis defects in zebrafish, a mutation disrupting cdk21 ( cyclin-dependent kinase 21 ) was identified, which caused gonad hypoplasia, reduced fertility and failure of female sex specification. The cdk21 gene is unique to fishes, though the encoded protein is related to the D-cyclin partners Cdk4 and Cdk6, which are known G1 cell cycle regulators. In the testis, cdk21 mutant germ cells exhibited cell cycle defects such as diminished proliferation, prolonged meiosis and delayed sperm differentiation. Furthermore, cdk21 mutants failed to maintain germ cells following breeding. Based on these findings, we propose that cdk21 regulates spermatogonial proliferation, progression through meiosis and germline stem cell activation in the testis. In addition, we investigated cdk4 and cdk6 in zebrafish development and found that each has distinct expression patterns in the gonads. Mutant analysis demonstrated that cdk6 was necessary for viability beyond larval stages. In contrast, cdk4 mutants were viable but were all male with low breeding success and sperm overabundance. Our analysis demonstrated that zebrafish harbor three genes of the cdk4/6 family, cdk4, cdk6 and cdk21, with cdk21 having an essential role in germ cell development in the testis.